The Job Requirements Information System for Rural Communities - Abubaker, Omar Mohammed (2009)
The rural communities take 37 percent of the population in Malaysia (9th Malaysia Plan, 2006), the income gap between the urban areas and the rural areas is very big. Even though the government has tried a lot of policies to develop the rural area, the income gap between the rural and urban continued to be wide. Many people live in the rural area try all means to go out and find a job since their job requirement can not be satisfied in the rural area. However, the problem of unemployment of the rural people is still very serious. The purpose of this study is therefore to understand and identify the job requirements of the rural community in Changlun. An online system will be proposed to store and manage information about job requirements for rural communities. With this system, the company can search for the employees they need and thus create more job opportunities for the rural communities. The information of the rural communities including their job requirements and ICT literacy can indicate the gap between their qualification and their desired job, so the specific training can be provided to rural communities to improve their competitive advantage and lead to job enlargement.